An integrated configurable quick string fastener device - Guan, Zhi Yong (2015)
In recent years, consumers’ increased exposure to the concept of Do-It-Yourself (DIY) through traditional and online media have led to a higher demand for DIY products. Despite a number of products in the market that offers consumers a solution for hanging modules, i.e. pictures, they often follow a fixed configuration and do not provide a one-off solution for easy rearrangement of modules. Therefore, the aim of this project is to offer consumers a string panel device that is integrated, configurable and functions as a quick string fastener, which provides consumers the flexibility and individuality fulfilled by DIY products through the autonomy to (re)arrange the modules without having to remove the string panel. The project consists of two main portions, the design development and the product development. The design development includes a review of existing literature on existing products, patents, materials and modules, the utilization of a systematic approach towards the design generation, and a criterial evaluation on developed conceptual designs and materials. Six evaluation criteria, namely safety, cost, aesthetic appearance, maintenance, ease of use and simplicity were studied and used to evaluate the four designs conceptualized. The designs were derived through the study of the form and structure of supporting panels, holding and adjusting devices, and locking systems and also from the valuable insights gained through the process of patent search, evaluation of existing hanging products and literature review on relevant materials and theories. The finalized design, after improvisation from the protruding brackets taken from the idea of shelves slotted with different dividers, adopted the combination of a washer and the M6 x 40.0 screw and nut assembly as the fastener component, they are to be made from stainless steel that is of high strength and resistance to corrosion and stain. Its purpose is to provide the tension needed in the nylon double braid rope to counter the weight of the modules to minimize deflection. The clamping mechanism of a lobster clip was also included in the final design to secure the rope in place to the two clear acrylic panel blocks which acts as supporting frames. The product development includes development of the prototype using the finalized design and materials and validation of the design parameters using theories and experiments to study the rope deflection due to multiple loads and load to tension ratio. Experiments were conducted using two support panels with a rope connected to each other. Loads were next added in to the cups attached to the rope and the resultant deflection was recorded. A deflection limit of 5cm was fixed as the gauge for the deflection parameter and results show that achieving a deflection of less than 5cm in reality was possible under a few conditions. Overall, the design of the integrated configurable quick string fastener device accommodates for different arrangements, numbers and sizes of modules, hence satisfying consumers’ increased need for selfhood. Findings also revealed that at a fixed load to tension ratio of no more than 1%, reliable estimations of the rope deflection in reality could be derived using the formula provided. While the project aims to develop a string device that is able to support multiple loads, further studies can focus improving the design by incorporating the screw thread length with the tension force in the rope.